The orthopaedic family day 2023: our strength lies in our unity! - Sikkandar, Mohamed Faizal (Faculty of Medicine, 2023)
On Saturday of 21st January 2023, the Department of Orthopedic and Traumatology UiTM held its inaugural Family Day Event in Kuala Selangor Cabin Camp (KSCC), Jeram, Selangor. The first-ever large-scale family event organized by the department for its members, supporting staff and doctors convened together in unison to celebrate the event.